Cybercrimes Between Criminalization and Punishment - Aziz, Turath; Mohammed, Ammar (Indonesian Journal of Law and Justice, 2025)
This research covers the Iraqi experience regarding cybercrimes, which reveal an obvious discrepancy between the present criminal laws and the widespread nature of the breaches that are common nowadays. This research particularly covers the ongoing use of the Code of Criminal Procedure and the 1980 Wireless Communications Law, despite the reality that the laws were mainly drafted for physical crimes. As such, the legislation doesn't address the wide range of other crimes that are committed using the internet, such as hacking into computer systems, the manipulation of electronic data, and international fraud. In addition, the research focuses on the problems faced by the prosecution regarding the search for electronic documentation, which, as discussed, remains uncharted despite plenty of gaps. In short, the whole criminal justice system only delivers ineffectual penalties despite the gravity of the crime. This research forms the starting point for exploring the gaps that are apparent within the existing Iraqi legal framework. It assesses the applicability of the laws and regulations and attempts to pinpoint where the laws are failing and why there are discrepancies in enforcing them. The authors believe that the criminalization process needs to shift from the imbalance of the laws to the definition of digital behaviors and an accompanying shift in the definition of the evidentiary rules. The conclusion reached highlights that Iraqi legislation and regulations lack the efficacy required to deal with the comprehensiveness of the threats that come through cyberspace.